Augustine: faith has its own eyes - Contaldo, Sílvia Maria (2022)
This article is a commentary on a text of St Augustine entitled De fide rerum quae non videntur, which is a sermon motivated by the misconceptions or even mistakes of those who do not profess the Christian faith. The text was probably written between 420-425 A.D., a time conducive to strengthening of faith in invisible things, given the historical horizon that heralded the decline of the Roman Empire. In the composition of the text, in line with the proper style of a sermon, there are eight brief parts. Without losing cohesion with regard to the main theme, Augustine concludes that faith has its own eyes capable of seeing – and allowing us to believe in – invisible things. Recebido: 30/12/2019Aceito: 30/12/2019